Distribusi Kemampuan Berpikir Matematik Tingkat Tinggi pada Siswa Sekolah Menengah Atas Kota Tasikmalaya Tahun Pelajaran 2018/2019 - Nugraha, Depi Ardian; Santika, Satya (Universitas Suryakancana, 2020)
ABSTRACTThis study aims to determine the distribution of higher-order mathematical thinking skills of students of state senior high schools in Tasikmalaya City in the academic year 2018/2019, to find out whether there is a relationship between mathematical critical thinking abilities with students' mathematical creative thinking skills High School in Tasikmalaya City 2018/2019 academic year. This research is a type of descriptive research using quantitative descriptive methods. The population in this study were all students of Tasikmalaya City Senior High School in class X, class XI, and class XII, ranging in age from 16-18 years. The sampling technique in this study uses a probability sampling technique that is Proportionate Stratified Random Sampling, by taking 2 classes each school. The research instrument used in this study was a matter of high-level mathematical thinking ability tests which are slices of the cognitive dimension of Bloom's Taxonomy with the 2013 Curriculum Dimension dimension consisting of questions of critical and creative thinking skills. The results showed that the distribution of mathematical thinking ability levels in high school students in the City of Tasikmalaya academic year 2018/2019 as follows: a) mathematical HOTS ability with a very good category was obtained by 2 Schools or 20% of all High School Schools in Tasikmalaya City, the ability Mathematical HOTS with the good category is obtained by 7 Schools or 70% of all High Schools in Tasikmalaya City, Mathematical HOTS ability with a pretty good category is obtained by 1 School, namely SMAN J or 10% of all Public High Schools in Tasikmalaya City. There is a significant relationship between students' mathematical critical thinking skills with the mathematical creative thinking abilities of high school students in the City of Tasikmalaya 2018/2019 academic year. with the degree of correlation obtained a correlation coefficient of 0.283 or are in a low category.Â Keywords: Higher Order Mathematical Thinking Skills, mathematical critical thinking skills, mathematical creative thinking skills.